Auxin: an emerging regulator of tuber and storage root development - Kondhare, Kirtikumar R.; Patil, Aruna B.; Giri, Ashok P. (Plant Science, 2021)
Many tuber and storage root crops owing to their high nutritional values offer high potential to overcome food security issues. The lack of information regarding molecular mechanisms that govern belowground storage organ development (except a tuber crop, potato) has limited the application of biotechnological strategies for improving storage crop yield. Phytohormones like gibberellin and cytokinin are known to play a crucial role in governing potato tuber development. Another phytohormone, auxin has been shown to induce tuber initiation and growth, and its crosstalk with gibberellin and strigolactone in a belowground modified stem (stolon) contributes to the overall potato tuber yield. In this review, we describe the crucial role of auxin biology in development of potato tubers. Considering the emerging reports from commercially important storage root crops (sweet potato, cassava, carrot, sugar beet and radish), we propose the function of auxin and related gene regulatory network in storage root development. The pattern of auxin content of stolon during various stages of potato tuber formation appears to be consistent with its level in various developmental stages of storage roots. We have also put-forward the potential of three-way interaction between auxin, strigolactone and mycorrhizal fungi in tuber and storage root development. Overall, we propose that auxin gene regulatory network and its crosstalk with other phytohormones in stolons/roots could govern belowground tuber and storage root development.
Keywords: Auxin; Potato; Storage root; Sweet potato; Tuber